POST-PEAK EGG PRODUCTION IN LOCAL AND IMPORTED STRAINS OF JAPANESE QUAILS (C OTURNIX COTURNIX JAPONICA) AS INFLUENCED BY CONTINUOUS AND INTERMITTENT LIGHT REGIMENS DURING EARLY GROWING PERIOD - A. S. Jatoi; M. K. Khan; A. W. Sahota; M. Akram; K. Javed; M. H. Jaspal; S. H. Khan (Journal of Animal and Plant Sciences, 2013)
A study was conducted at Avian Research and Training Centre, University of Veterinary and Animal Sciences, Lahore to investigate earlier effect of continuous and intermittent lights in 3 local and one imported close-bred flocks of Japanese quails (Coturnix coturnix japonica) on their post-peak egg production. Day-old quails were provided continuous 24 hours light up to first 2 weeks and were maintained under 5 different light treatments, A (16L: 8D), B (8L: 6D: 2L: 8D), C (8L: 7D: 1L: 8D), D (8L :7.5D: 0.5L: 8D) and E (8L: 16D) from 3rd to 14th weeks and from 15th weeks onward provided light 16L: 8D. In this trial, 22 weeks-old 240 quails of the same treatments were kept from 23 to 34 weeks under factorial arrangements (5 lights x 4 close bred flocks x 3 replicates of 1 male: 3 females each in a 5 tier battery) under same management. The results showed significant effect of light treatments on body weight (p<0.01), feed intake (p<0.01), egg production (p<0.05) feed conversion ratio (feed/dozen egg) and FCR (feed/ egg) (p<0.01). The highest body weight was recorded under treatment B, however, A, C, D and E differed non-significantly. Higher feed intake was observed under treatment A, varying non-significantly with treatment D. The birds in group A produced significantly (p<0.05) more eggs than in other experimental treatments. FCR in group E was significantly (p<0.05) better than in all other light treatments. Light and strain interaction was significant (p<0.01). The quail strains differed in the above parameters.
Keywords: Light regimens; body weight; egg production; egg weight; feed intake; FCR